Insulin sensitivity improvement of fermented Korean Red Ginseng (Panax ginseng) mediated by insulin resistance hallmarks in old-aged ob/ob mice - Jeong-Mu Cheon (Journal of Ginseng Research, 2015)
Background: The biological actions of various ginseng extracts have been studied for treating obesity and diabetes mellitus. However, few studies have evaluated the effects of fermented Korean Red Ginseng (Panax ginseng Meyer) on metabolic syndrome. The present study evaluated the antiobesity and antidiabetic effects of fermented red ginseng (FRG) on old-aged, obese, leptin-deficient (B6.V-Lepob, “ob/ob”) mice. Methods: The animals were divided into three groups and given water containing 0%, 0.5%, and 1.0% FRG for 16 wk. The effect of FRG on ob/ob mice was determined by measuring changes in body weight, levels of blood glucose, serum contents of triglycerides, total cholesterol and free fatty acids, messenger RNA (mRNA) expressions of key factors associated with insulin action, such as insulin receptor (IR), lipoprotein lipase (LPL), glucose transporter 1 and 4 (GLUT1 and GLUT4), peroxisome proliferators-activated receptor gamma (PPAR-γ), and phosphoenolpyruvate carboxykinase (PEPCK) in the liver and in muscle, and histology of the liver and pancreas. Results: FRG-treated mice had decreased body weight and blood glucose levels compared with control ob/ob mice. However, anti-obesity effect of FRG was not evident rather than hypoglycemic effect in old aged ob/ob mice. The hyperlipidemia in control group was attenuated in FRG-treated ob/ob mice. The mRNA expressions of IR, LPL, GLUT1, GLUT4, PPAR-γ, and PEPCK in the liver and in muscle were increased in the FRG-treated groups compared with the control group. Conclusion: These results suggest that FRG may play a vital role in improving insulin sensitivity relative to reducing body weight in old-aged ob/ob mice.